Cardosin A contains two vacuolar sorting signals using different vacuolar routes in tobacco epidermal cells. (8th August 2013) - Pereira, Cláudia; Pereira, Susana; Satiat‐Jeunemaitre, Béatrice; Pissarra, José
Summary Several vacuolar sorting determinants (VSDs) have been described for protein trafficking to the vacuoles in plant cells. Because of the variety in plant models, cell types and experimental approaches used to decipher vacuolar targeting processes, it is not clear whether the three well‐known groups of VSDs identified so far exhaust all the targeting mechanisms, nor if they reflect certain protein types or families. The vacuolar targeting mechanisms of the aspartic proteinases family, for instance, are not yet fully understood. In previous studies, cardosin A has proven to be a good reporter for studying the vacuolar sorting of aspartic proteinases. We therefore propose to explore the roles of two different cardosin A domains, common to several aspartic proteinases [i.e. the plant‐specific insert (PSI) and the C–terminal peptide VGFAEAA] in vacuolar sorting. Several truncated versions of the protein conjugated with fluorescent protein were made, with and without these putative sorting determinants. These domains were also tested independently, for their ability to sort other proteins, rather than cardosin A, to the vacuole. Fluorescent chimaeras were tracked in vivo, by confocal laser scanning microscopy, in Nicotiana tabacum cells. Results demonstrate that either the PSI or the C terminal was necessary and sufficient to direct fluorescent proteins to the vacuole, confirming that they are indeed vacuolar sorting determinants. Further analysis using blockage experiments of the secretory pathway revealed that these two VSDs mediate two different trafficking pathways.